1971
DOI: 10.1002/aja.1001300307
|View full text |Cite
|
Sign up to set email alerts
|

The fine structure of perinotochordal microfibrils in control and enzyme‐treated chick embryos

Abstract: A B S T R A C TMicrofibrils in the notochordal sheath of chick embryos of two to four days incubation age were analyzed electron microscopically. Collagenase, trypsin, hyaluronidase and alpha amylase were administered to both "living" and "fixed" embryos. Living embryos were either explanted on an agar-albumen growth medium or were allowed to survive within the shell during experimental procedures. Fixed embryos were immersed in Karnovsky's aldehyde fixative prior to enzyme digestion. Both living and fixed spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

1971
1971
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(13 citation statements)
references
References 47 publications
0
12
0
1
Order By: Relevance
“…Different extracellular matrix molecules, mainly proteoglycans and basement membrane proteins, have been identified within the sheath (see for discussion O'Connell and Low 1970;Frederickson and Low 1971;Ruggeri 1972;Carlson and Kenney 1980;Götz et al 1995a, b). A cartilage-like collagen II was likewise found in Xenopus notochordal sheath (Seufert et al 1994) and was proposed to mediate neurocranial morphogenesis.…”
Section: Discussionmentioning
confidence: 98%
“…Different extracellular matrix molecules, mainly proteoglycans and basement membrane proteins, have been identified within the sheath (see for discussion O'Connell and Low 1970;Frederickson and Low 1971;Ruggeri 1972;Carlson and Kenney 1980;Götz et al 1995a, b). A cartilage-like collagen II was likewise found in Xenopus notochordal sheath (Seufert et al 1994) and was proposed to mediate neurocranial morphogenesis.…”
Section: Discussionmentioning
confidence: 98%
“…The amount of granules, on the contrary, was constant during the whole migratory process. Cytochemical studies performed in the migratory pathways of bird neural crest cells revealed filaments that were also removed after hyaluronidase treatment (Frederickson and Low 1971;Hay 1978). Similar filaments were observed Table 1 The total length of ruthenium hexammine trichloride-positive filaments per area (3.6 µm 2 ) of the extracellular space of the migratory pathway of mouse embryo primordial germ cells.…”
Section: Discussionmentioning
confidence: 99%
“…Except for seven whole eyes fixed in Bouin's fluid for light microscopy, anterior half-eyes were dissected out and the posterior surface of the iris cleaned with watchmaker's forceps. These freshly dissected tissues were treated with enAbbreviations H enzyme treatment, hyaluronidase only HC enzyme treatment, hyaluronidase followed by collagenase, series two only M macrophage NE no enzyme treatment zymes as follows: (1) no enzyme treatment; (2) testicular hyaluronidase (bovine testis, Sigma type I-S, 500 U/ml) in 80% Dulbecco's PBS (Gibco) at pH 5.2 for 30-45 min at room temperature; (3) hyaluronidase as above followed by a rinse in PBS and treatment with 0.1% collagenase (Clostridium, Sigma type I-A) in 80% Dulbecco's PBS at pH 6.8 for 45-60 min at room temperature (Frederickson and Low, 1971). Following these treatments, the specimens were rinsed in PBS and fixed in Karnovsky's fixative in 0.1 M Na cacodylate buffer at pH 7.3 for 3 h r a t room temperature or 30-90 min at room temperature followed by 4°C overnight.…”
Section: Methodsmentioning
confidence: 99%